Pedagogical Mechanisms of Forming a Healthy Lifestyle in Primary School Students - Mansurovich, Salikhov Timur (International Journal on Integrated Education, 2023)
This article covers the main issues of healthy physical education, proper nutrition, and the main mechanisms of teaching elementary school students to a healthy lifestyle.